Challenges of the Resource-Based View Approach in Improving Business Organizational Performance - Shinta Salsabila; Radhiana Radhiana; Juwita Juwita; Putri Mauliza (International Conference on Multidisciplinary Research, 2022)
The resource-based view is the predominant theoretical paradigm in strategic management research (RBV). In this essay, the positioning literature is reviewed, and it is investigated to what degree the RBV may be used as a source of useful advice for businesses looking to gain a competitive edge and achieve strategic success. Human, organizational, and physical resources are all studied in relation to organizations. It will be clear how this organizational resource affects the competitive advantage of the business. The research methodology employed is based on a literature review approach from the views of specialists who examine the RBV theory in relation to capabilities and competencies in fostering superior competitiveness. This study gives a general overview of the traits of the resource approach, which supports strategic management and strengthens businesses' capacities and competences to gain competitive advantage through the use of resources, both physical and non-physical. The uniqueness of the resources owned, both tangible and intangible assets, is examined in this study in order to support management decision-making regarding the competitive advantage of a business organization. This study also analyses the various viewpoints of economists regarding the resource framework that can generate capabilities. Keywords: Resource-Based View (RBV), Competitive Advantage, Tangible Intangible Assets.